Nanohydroxyapatite Silicate-Based Cement Improves the Primary Stability of Dental Implants: An In Vitro Study - Hooman Khorshidi; Saeed Raoofi; Maryam Najafi; Mohammad Hassan Kalantari; Jamshid Khorshidi Malahmadi; Reza Derafshi (Advances in Materials Science and Engineering)
Objectives. Insufficient cortical bone volume when placing implants can lead to lack of primary stability. The use of cement as a bone fill material in bone defects around dental implant could result in better clinical outcome. HA has shown excellent biological properties in implant dentistry. The purpose of this study was to evaluate the effect of nanohydroxyapatite powder (Nano-HA) in combination with accelerated Portland cement (APC) on implant primary stability in surgically created circumferential bone defects in a bovine rib in vitro model. Materials and Methods. Sixteen bovine rib bones and thirty-six implants of same type and size (4 mm × 10 mm) were used. Implants were divided into six groups: no circumferential bone defect, defect and no grafting, bone chips grafting, Nano-HA grafting, APC grafting, and Nano-HA mixed to APC grafting (Nano-HA-APC). Circumferential defects around the implants were prepared. The implant stability quotient (ISQ) values were measured before and after the grafting. Results. APC exhibited the highest ISQ values. A significant increase of ISQ values following the grafting of Nano-HA-APC (18.08±5.82) and APC alone (9.50±4.12) was achieved. Increase of ISQ values after 72 hours was 24.16±5.01 and 17.58±4.89, respectively. Nano-HA grafting alone exhibited the least rise in ISQ values. Conclusions. Nanohydroxyapatite silicate-based cement could improve the primary stability of dental implants in circumferential bone defect around implants.